The Effect of A Training Program On Developing Motor Response Speed While Performing Some Basic Skills In Handball - Khenjer, Raad (Journal of Physical Education, 2010)
The sport of handball is rich with varieties in performances, skills and the repetitions of defensive and offensive skills. It depends on the player's abilities, skills and tactics to achieve the best results. The speed of motor response is one of the abilities that play an important role in performing the basic skills and defensive and offensive tactics. Thus the researcher came up with a training program that will develop the speed of motor response while performing the basic skills in handball. The aim of the research is to identify the effect of the training program on the development of skill performance. The researcher used the experimental method. The subjects were (16) handball players from Al Jaish Athletic club. The researcher came up with many conclusions; the most important one is that the training program has a positive effect in developing the basic skills of handball. Finally, he recommended that the proposed training program should be used by coaches to develop the players' performance and making similar studies on other subjects.